Figurações dos preconceitos e da marginalidade em Clara dos Anjos - ALMEIDA, Isis Maia de (2015)
This work reflects on the figurations of prejudice and marginality in the novel Clara dos Anjos, Lima Barreto, understanding that prejudice is one of the evil factors of social relationships, which leads to exclusion and therefore marginality. It is understood as marginal, in this thesis, the individual who for various reasons, is delayed, deleted, but not being related necessarily to the commission of unlawful acts. The creator of Clara dos Anjos is considered here as a marginal author, to live on the outskirts of Rio de Janeiro, being black, poor, and suffer the consequences of stigma. Moreover, it is stated that is a precursor of today's authors Marginal Peripherals such as Ferréz and Sérgio Vaz. This is the bias in some of its aspects, starting from elements and aspects detected in literary analysis of the novel Clara dos Anjos. For this purpose, intending to deepen this overlapping of prejudice against social exclusion (one of the main aspects of "marginality" as is understood here), I tried to deepen reflections on the main aspects of prejudice suffered by Lima Barreto and his work: social prejudice, itself - focusing on poverty issues -; the gender; the race and language. They have been key drivers as thematic thread, identity aspects of the "Era of Globalization" and the issue of marginalization in contemporary literature. One of the working assumptions is centered on the fact that Lima Barreto was considered sloppy, in literary terms, by some important critics of his day. As a result, the work limabarretiana was classified for decades, such as lower by differentiating the traditional standard literature. The emphasis is also the problem of prejudice in relation to language, because it remains a tool in the service of social hierarchies. In practice, anyone who does not fit the established pattern can be considered "subordinate" - to remember the term used by Gayatri Spivac in his book Can the subaltern speak? Finally, this paper presents an interdisciplinary, literature and interpretive approach. Seeks to contributions from various fields of knowledge, emphasizing the reflections in the field of Portuguese Language, Literature, Anthropology, History, with the most relevant theoretical scope of the works of Stuart Hall; Zygmunt Bauman, Carlos Bagno, Gayatri Spivak; Alfredo Bosi; Joel Rufino dos Santos, Erica Peçanha do Nascimento and João César de Castro Rocha.